A promising approach to an environmentally friendly pest management solution: nanocarrier-delivered dsRNA towards controlling the destructive invasive pest Tuta absoluta. Issue 4 (8th March 2023) - Wang, Xiaodi; Ji, Shunxia; Bi, Siyan; Tang, Yanhong; Zhang, Guifen; Yan, Shuo; Wan, Fanghao; Lü, Zhichuang; Liu, Wanxue
Abstract : Nanocarrier-delivered dsRNA can be a promising environmentally friendly pest management solution. Abstract : To develop an environmentally friendly pest controlling RNAi method for the destructive invasive pest Tuta absoluta, we analysed the binding ratio between the nanocarrier and dsRNA, performed morphological characterization, investigated stability, leaf absorption rate and insect wall permeability of dsRNA–nanoparticle complexes, in addition to exploring the RNAi controlling effect and the safety risk analysis. Chitosan (CS) and star polycation (SPc) may be loaded with dsRNA, and the optimum fusion at dsRNA to CS and SPc mass ratios of 12.5 : 1 and 1 : 1, respectively. The morphology characterization was changed from chain-like dsRNA to spherical dsRNA–nanoparticle complexes, and the size became smaller. Nanomaterials effectively protect dsRNA from nuclease degradation, and significantly improved the leaf penetration efficiency. Furthermore, they penetrated the epidermis to enter the insect gut. Moreover, dskr-h1 /CS and dskr-h1 /SPc complexes, applied as a foliar spray, were fed to T. absoluta larvae and both complexes resulted in a significant reduction in pupal weight and emergence rate. Additionally, safety risk analysis showed that the dskr-h1 target gene had no effect on the non-target organism N. tenuis, and was safe for the environment. The target gene had no match sequence with humans or known predacity and parasitical enemies in the same ecological niche. In conclusion, the results first indicated that CS and SPc nanomaterials could successfully mediate specific target dsRNA delivery in T. absoluta, and dsRNA–nanoparticle complexes could be used to control the tomato leaf miner. The study confirmed and enriched that nanocarrier-delivered RNAi system could successfully be used for controlling pests other than model insects, providing a basis for the development of green, safe, efficient, and sustainable control of other pests.